(untitled) (Pain medicine, 2017)
Today, the concept of problem-oriented treatment (point-of-care) is widely used in patients with acute pathology, urgent conditions, including cardiac arrest. Of course, not only cardiologists are in contact with cardiologic patients, but many other specialists (emergency medicine physicians, therapists, intensive care specialists, anesthetists), for whom the answer to the clinical question followed by choosing treatment tactics is important. The article covers the use of BLUE-protocol and Focus-protocol, which allow to quickly and accurately diagnose most of the complications that arise in critical conditions, including states accompanied by severe pain syndrome, that greatly improves and clarifies the following therapeutic tactics, including anesthesia.